GA3, a new gambogic acid derivative, exhibits potent antitumor activities in vitro via apoptosis-involved mechanisms - Xie Hua; Qin Yu-xin; Zhou Yun-long; Tong Lin-jiang; Lin Li-ping; Geng Mei-yu; Duan Wen-hu; Ding Jian (Acta Pharmacologica Sinica, 2016)
Aim: Gambogic acid (GA) is the major active ingredient of gamboge, which is secreted from a Chinese traditional medicine, Garcinia hanburyi, which possesses potent antitumor activity. GA3, a new GA derivative, has been shown to possess better water solubility than GA. The aim of the present study was to examine the antitumor activity of GA3 and the mechanism underlying it. Methods: The growth inhibition of cancer cell lines induced by GA3 was assessed using the SRB assay. DAPI staining, flow cytometry, a DNA fragment assay, and Western blot analysis were used to study the apoptotic mechanisms of GA3. Results: GA3 displayed wide cytotoxicity in diversified human cancer cell lines with a mean IC50 value of 2.15 μmol/L. GA3 was also effective against multidrug resistant cells, with an average resistance factor (RF) that was much lower than that of the reference drug, doxorubicin. Mechanistic studies revealed that GA3-induced apoptosis in HL-60 cells proceeded via both extrinsic and intrinsic pathways, with caspase-8 functioning upstream of caspase-9. In addition, GA3-driven apoptotic events were associated with up-regulation of Bax, down-regulation of Bcl-2 and cleavage of Bid. Moreover, GA3 triggered cytochrome c release from the mitochondria, in particular bypassing the involvement of the mitochondrial membrane potential. Conclusion: Better solubility and a potential anti-MDR activity, combined with a comparable antitumor efficacy, make GA3 a potential drug candidate in cancer therapy that deserves further investigation.